2018
DOI: 10.1055/s-0038-1654710
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tracheostomy in Intensive Care Unit Patients

Abstract: Introduction  The ideal timing of tracheostomy in intensive care units (ICUs) for critically ill patients undergoing prolonged mechanical ventilation (MV) is still a controversial issue. Objectives  To determine the proper timing of tracheostomy and its impact on various clinical outcomes of adult patients in ICUs undergoing prolonged MV. Methods  The present study consisted of a sample of 67 ICU adult patients who were submitted to open surgical tracheostomy and divided into two groups: 30 patients in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…The various retrospective studies 25,28,42,43,51,52 conducted in different patient subsets also confirmed that the timing of tracheostomy does not reduce in hospital mortality.…”
Section: Does Early Tracheostomy Reduce the Mortality In Critically Imentioning
confidence: 75%
“…The various retrospective studies 25,28,42,43,51,52 conducted in different patient subsets also confirmed that the timing of tracheostomy does not reduce in hospital mortality.…”
Section: Does Early Tracheostomy Reduce the Mortality In Critically Imentioning
confidence: 75%
“…Although these studies did not stratify patients based on tracheostomy timing or technique, these results suggest that patient comorbidities may be one of the more consistent prognosticators for tracheostomy patients, especially given that tracheostomy patients are likely to be in critically ill conditions caused by a wide array of disease processes. [35][36][37] Interestingly, unknown partner status (e.g., not knowing whether a patient is single, married, divorced) was associated with decreased survival. Several studies have demonstrated an association between unpartnered status (single, divorced, separated, widowed) and negative health outcomes-and similarly an association between partnered status (married, significant other) and improved health outcomes-in a variety of patient populations with diverse underlying disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…2 As previously reported, early tracheostomy within 10 days has shown beneficial effects in terms of early liberation from mechanical ventilation and heavy sedation. 26 In our experience, PT was feasible and safe for the medical team and the majority of our patients. A brief survey among the intensivists who performed the PT in our patients revealed the difficulty related to wearing full PPE as the most challenging condition in this setting.…”
Section: Discussionmentioning
confidence: 59%
“…As previously reported, early tracheostomy within 10 days has shown beneficial effects in terms of early liberation from mechanical ventilation and heavy sedation. 26 …”
Section: Discussionmentioning
confidence: 99%